The influence of cow and management factors on reproductive performance of Irish seasonal calving dairy cows - Lane, Elizabeth A; Crowe, Mark A; Beltman, Marijke E; More, Simon J (Animal reproduction science, 2013)
Herd management record analysis facilitates accurate assessment of the current herd reproductive status; a crucial decision making tool to implement effective change. To determine the relative importance of cow and management factors on reproductive indices in moderate-yielding Irish seasonal-calving dairy herds, breeding records of 1173 cows were collected from 10 seasonal calving herds between 2007 and 2009. Backward-stepwise multivariable logistic regression analysis was utilised to determine the effect of cow factors including parity, calving timing, days post partum, heat detection accuracy and herd factors including herd size and heat detection efficiency on key reproductive indices. Mean farm six-week pregnancy and end of season not-in-calf rate were 46% (range 14–72%) and 22% (range 3–40%), respectively. Oestrous detection efficiency (P<0.001), timing of calving (P<0.001) relative to start of breeding, history of abnormal repeat intervals (P<0.001) and length of post partum interval (P<0.001) were each associated with lower six-week pregnancy rates. Timing of calving (P<0.001) and history of abnormal repeat intervals (P<0.001) were associated with higher not-in-calf rates. Herd size and cow parity were not associated (P>0.05) with either outcome when factors including existing calving pattern and heat detection accuracy and efficiency were accounted for. The existing spread in calving pattern, heat detection quality and length of voluntary waiting period were the most influential factors that reduced fertility performance in seasonal-calving herds.